2016
DOI: 10.1108/er-03-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Fun times: the relationship between fun and workplace engagement

Abstract: Purpose – The idea of workplace fun seems positive, straightforward and simple but emerging research suggests a surprising complexity and ambiguity to this concept. Drawing on recent literature and empirical data, the purpose of this paper is to use three different forms of workplace fun: managed, organic and task fun to examine the relationship between fun and workplace engagement. Design/methodology/approach – Using an ethnographic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 49 publications
3
109
0
Order By: Relevance
“…There is some linking of the concepts of engagement and fun in the suggestion that for engaged employees actual work becomes fun and Gorgievski and Bakker (2010, p. 265) differentiate workaholism and work engagement by the positive aspect of fun associated with engagement. However, there is surprisingly little discussion of fun as a component of engagement and this is an area for future development (see Plester and Hutchison, 2012).…”
mentioning
confidence: 99%
“…There is some linking of the concepts of engagement and fun in the suggestion that for engaged employees actual work becomes fun and Gorgievski and Bakker (2010, p. 265) differentiate workaholism and work engagement by the positive aspect of fun associated with engagement. However, there is surprisingly little discussion of fun as a component of engagement and this is an area for future development (see Plester and Hutchison, 2012).…”
mentioning
confidence: 99%
“…In addition, they found that the implementation strategy of moderate positive relationship between the three organizational resources and the involvement of collective organization. While, [28], suggested to the effects on an organizational level, creating an enjoyable workplace that stimulates pleasure greater overall involvement with the team, unit or organization it self.…”
Section: Organization Engagementmentioning
confidence: 99%
“…Workplace fun has been linked with job engagement notably in Plester's and Hutchison's (2016) approach, who found that employees associated the concept of engagement when talking about fun, and associated both with positive feelings. In specific, Plester and Hutchison (2016) revealed that the two concepts are linked through the positive feelings that are generated towards the organization and the team, which in turn increase organizational engagement. Both workplace fun and job engagement are characterized by enthusiasm and positive energy that function as motivational processes and help employees deliver more positive outcomes.…”
Section: Contextual Performancementioning
confidence: 99%